2008
DOI: 10.1002/art.23701
|View full text |Cite
|
Sign up to set email alerts
|

Klinefelter's syndrome (47,XXY) in male systemic lupus erythematosus patients: Support for the notion of a gene‐dose effect from the X chromosome

Abstract: Objective. Systemic lupus erythematosus (SLE) is a systemic autoimmune disease that predominantly affects women. Despite isolated reports of patients with coexisting Klinefelter's syndrome (47,XXY) and SLE, no association of Klinefelter's syndrome with SLE or any other autoimmune disease has been established. The present study was undertaken to investigate the prevalence of Klinefelter's syndrome in a large population of patients with SLE.Methods. Sex chromosome genotyping was performed in 981 SLE patients, of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
242
1
8

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 338 publications
(269 citation statements)
references
References 70 publications
7
242
1
8
Order By: Relevance
“…Indeed, data from Scofield et al suggest that men with Klinefelter's syndrome (47, XXY) have a similar risk to develop lupus as normal women (46, XX) and ~14 times higher risk to develop lupus compared to normal men (46,XY). 19,20 These data reinforce the idea of a gene-dose effect on the X-chromosome for the risk to develop lupus. This genedose effect may be achieved by hypomethylation of the X chromosome, making more than one X chromosome available for transcription.…”
Section: O N O T D I S T R I B U T Esupporting
confidence: 72%
“…Indeed, data from Scofield et al suggest that men with Klinefelter's syndrome (47, XXY) have a similar risk to develop lupus as normal women (46, XX) and ~14 times higher risk to develop lupus compared to normal men (46,XY). 19,20 These data reinforce the idea of a gene-dose effect on the X-chromosome for the risk to develop lupus. This genedose effect may be achieved by hypomethylation of the X chromosome, making more than one X chromosome available for transcription.…”
Section: O N O T D I S T R I B U T Esupporting
confidence: 72%
“…Furthermore, many authors published one or more cases with association of both KS and SLE, and its various manifestations Recently, a large genotyping study in SLE patients revealed that of the 213 SLE men, five had KS (47, XXY) genotype. The risk of SLE in men with 47, XXY genotype has been calculated to be approximately 14-times higher than in men with 46, XY genotype, consistent with the notion that SLE susceptibility is partially explained by an X chromosome gene-dose effect (Scofield et al, 2008). Such effect could be mediated by abnormal inactivation of genes on the X chromosome, as has been demonstrated for CD40L, or by genetic polymorphism as has been demonstrated for Xq28.…”
Section: Ks and Systemic Lupus Erythematosus (Sle)supporting
confidence: 71%
“…Male patients with SLE, although rare, tend to have more severe disease and poorer outcome (2), suggesting potential sex dimorphism in the disease development. Although the sex effect has often been attributed to sex hormones, the fact that XXY male subjects have approximately a 14-fold higher risk of developing SLE than 46 XY men indicates that X-linked genes may be risk factors for human SLE (3).…”
mentioning
confidence: 99%